Books Received - Aurele La Rocque (Hello World!, 1974)
SHOUP, Charles S. (1974) A Bibliography of the Zoology of Tennessee and the Tennessee Valley Region. U.S. Atomic Energy Commission. Office of Information Services. Technical Information Center. iv, 251 p.